DEVELOPMENT OF DIGITAL LEARNING MATERIALS FOR COMPUTERIZED ACCOUNTING SUBJECT AT SMK PERMATA HARAPAN BATAM - Widijaya Widijaya; Melissa Melissa (Universitas Internasional Batam, 2022)
The government's decision in changing school learning system from face-to-face to remote/online learning, has implications for a total change for both students and teachers. Thus, it is difficult for schools to provide learning materials, modules or books that students receive optimally. The implementation of community service aims to solve the problems at SMK Permata Harapan Batam and in-depth observations and interviews have been carried out concerning the learning system. The problem faced by SMK Permata Harapan Batam during this pandemic is the lack of digital learning materials for MYOB computerized accounting for online learning which has now become school education system. Digital teaching material for computerized accounting are designed according to the problems that occur in the form of modules in Microsoft PDF, Microsoft PowerPoint, and case example in the form of computerized accounting learning videos in order to make it easier for students to understand the material while helping teachers in the teaching process. The composing of module in this project also adapts to the latest curriculum. This project contributes directly to the development of the learning system due to the COVID-19 pandemic for students and schools.